The impact of sowing date, production area and nutrient supply on the yield and quality parameters of millet - Seres, Emese (Acta Agraria Debreceniensis, 2014)
The millet is a very special plant with good adaptation that gives the possibility for the late sowing and secondary production. However the effects of late sowing modifies to the efficiency of the agrotechnological elements. The examinations – focused on this aspect – was conducted in the DU CAS RINY in the small plots in four replications in 2013. The largest effect was recorded in the sowing time of the examined factors (sowing time, nutrient supply, growing area). The effectiveness of the agrotechnological elements decreases under unfavourable circumstances caused by the late sowing. The examined factors did not affect in the protein content and milling rate, except in the latest sowing time when protein content was significantly the highest.